Neuroproteksi Otak Janin pada Persalinan Preterm dan Pertumbuhan Janin Terhambat - Bachnas, Adrianes (PT Dexa Medica, 2020)
Exalted obstetrics not merely fulfill the obligation to deliver babies safely but beyond, to deliver babies on their most optimal condition to grow up and to be a noble person. Neuroprotection should be implemented in daily practice. Brain, as the central part of the human body, plays an extremely important role for all of the human cells, tissue, organs, and systems activities. Any kind of physiological process in human body is related to brain control. There would be no human in optimal condition without optimal brain function. Preterm delivery and fetal growth restriction are two of the many pathologic conditions in pregnancy that could potentially injure fetal brain. Injured brain would result in major lifelong neurological deficits. There isn’t any cure for these, so prediction and prevention are barely necessary. Neuroprotection is a concept which all efforts are given to minimize the insult to the fetal brain due to such pathologic problems as mentioned before. Preterm birth, either spontaneously or iatrogenic, puts the risk for fetus to get brain damage. Hypoxic situations in the early minutes after birth lead to inflammation and apoptosis process, causing neuronal injury, neuronal death, and demyelination. Antenatal magnesium sulfate administration has found to give significant aid to hinder this condition and in the end showing a substantial reduction in the number of cerebral palsy cases. Fetal growth restriction remains an unsolved dilemma in maternal-fetal medicine. It is mostly related with placental insufficiency that causes chronic hypoxia and nutrition deprivation. Low dose aspirin in the first trimester soon as the poor placentation is known to be happen remains the solid evidence exists. Nutritional intervention such as a balanced intake of protein and calory, also micronutrients supplementation are somehow still worthy enough to accompany the timely decision of terminating pregnancy.